ajutorrrrr: 8^4÷(-4)^6+(-2)÷(-2)^0
Răspunsuri la întrebare
Răspuns de
4
Răspuns:
Explicație pas cu pas:
(-2)^0 = 1
8^4 = (2^3)^4 = 2^12
(-4)^6 = 4^6 = (2^2)^6 = 2^12
8^4÷(-4)^6 = 2^12÷2^12 = 1
(-2)÷(-2)^0 = -2 ÷ 1 = -2
1 - 2 = -1
Răspuns de
5
Răspuns:
Explicație pas cu pas:
8⁴ : ( - 4)⁶ + ( - 2 ) : ( - 2)⁰ = - 1
= ( 2³)⁴ : ( -2²)⁶ + ( - 2 ) : 1 =
= 2⁽³ˣ⁴⁾ : ( - 2)²ˣ⁶ - 2 =
= 2¹² : ( -2)¹² - 2 =
= 2⁽¹²⁻¹²⁾ - 2 =
= 2⁰ - 2 =
= 1 - 2 =
= - 1
Alte întrebări interesante
Geografie,
8 ani în urmă
Fizică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă